Influence of heat treatment on the nanocrystalline structure of ZnO film deposited on p-Si - Caglar, Yasemin; Ilican, Saliha; Caglar, Mujdat; Yakuphanoğlu, Fahrettin; Wu, Junshu; Gao, Kun; Xue, Dongfeng (Elsevier Science Sa, 2009)
The influence of heat treatment on the crystal structure, grain growth kinetics, orientation, and refractive index properties of the ZnO film deposited onto p-type single-crystalline Si substrate by sol-gel method has been investigated. The ZnO film has polycrystalline structure with a preferential growth along the (001) direction. X-ray diffraction analysis of the as-grown ZnO film showed a strong ZnO (002) diffraction peak centered at 34.398 degrees with a full width at half-maximum (FWHM) of 0.387 degrees. Annealing at 750 degrees C reduced the FWHM of the (002) diffraction peak to 0.188 degrees. The grain size of crystallites was calculated using the well-known Scherrer's formula and the grain growth mechanism for the ZnO film was analyzed. It was found that the grain growth in ZnO film was controlled by the grain boundary curvature mechanism. Texture coefficient, dislocation density and lattice constants of the ZnO films were calculated. The important changes in crystalline structure of the ZnO films were observed due to the heat treatment. The structural quality of ZnO films was improved by heat treatment process. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: ZnO film; Sol-gel processes; Optical properties; Annealing; Refractive index